Major ions in Central European precipitation - Insight into changes in NO3-/SO42-, NH4+/NO3- and NH4+/SO42- ratios over the last four decades - Hůnová, Iva; Brabec, Marek; Malý, Marek (Chemosphere, 2024)
Knowledge of precipitation composition is important, among other things, to reveal changes in atmospheric chemistry. Here we present the long-term time trends in ratios of major ions in precipitation, namely nitrate to sulphate (NO3-/SO42-), ammonium to sulphate (NH4+/SO42-) and ammonium to nitrate (NH4+/NO3-). For this we explore the long-term time series recorded by the Czech Hydrometeorological Institute at eight monitoring sites situated in urban, rural and mountain regions of the Czech Republic between 1980 and 2020. To that end, we use innovative Bayesian inference with the Integrated Nested Laplace Approximation (INLA) computational method appropriate for investigating complicated large-scale data. Our results indicated: (i) increasing NO3-/SO42- ratio in precipitation over time and distinct seasonal behaviour with higher values in winter and lower values in summer, (ii) increasing NH4+/SO42- ratio in precipitation and distinct seasonal behaviour with higher values in summer and lower values in winter and (iii) relatively stable NH4+/NO3- ratio in precipitation with a mild recent increase and distinct seasonal behaviour with higher values in summer and lower values in winter. This behaviour pattern holds true for all the sites analysed, irrespective of their geographical position, altitude or environment. Though explored in detail rarely, the ion ratios are important to study as they reflect changes in atmospheric chemistry, mirroring changes in emissions and meteorology and suggesting changing impacts on ecosystems and the environment.
Keywords: Bayesova věta; Seasons; ionty; monitorování životního prostředí; Bayes Theorem; roční období; Ion concentrations; INLA; Ions; Precipitation chemistry; látky znečišťující vzduch; Time trends; sírany; Sulfates; Bayesian modelling; ekosystém; amoniové sloučeniny; Ecosystem; Czech Republic; Nitrates; Ammonium Compounds; Air Pollutants; dusičnany; Environmental Monitoring